Severe Legionella pneumophila pneumonia treated with extracorporeal membrane oxygenation (ECMO): A case report - Kurdyś, Paulina; Ślusarz, Krystian; Trejnowska, Ewa (Journal of Education, Health and Sport, 2019)
Legionella pneumophila is an aerobic, Gram-negative bacterium, whose natural environment are aquatic reservoirs. The source of infection may be also tap water, fountains and air-conditioners. Among young people, it can cause only mild infections, however a lot of patients must be admitted to the hospital, of which 10% require a stay in the intensive care unit. Legionella pneumophila infection can manifest as severe, multi-lobe and bilateral pneumonia, which can lead to acute respiratory distress syndrome (ARDS).We describe the case of a 26-year-old male patient with Legionella pneumophila pneumonia treated with the use of extracorporeal membrane oxygenation (ECMO).